Relationship of hospital volume on outcomes in patients with acute pulmonary embolism: Analysis of a 70, 000 patient database. (February 2021) - Finkelstein, Mark; Cedillo, Mario A; Kestenbaum, David C; Shoaib, Obaib S; Fischman, Aaron M; Lookstein, Robert A
Positive relationships between volume and outcome have been seen in several surgical and medical conditions, resulting in more centralized and specialized care structures. Currently, there is a scarcity of literature involving the volume–outcome relationship in pulmonary embolism (PE). Using a state-wide dataset that encapsulates all non-federal admissions in New York State, we performed a retrospective cohort study on admitted patients with a diagnosis of PE. A total of 70, 443 cases were separated into volume groups stratified by hospital quartile. Continuous and categorical variables were compared between cohorts. Multivariable regression analysis was conducted to assess predictors of 1-year mortality, 30-day all-cause readmission, 30-day PE-related readmission, length of stay, and total charges. Of the 205 facilities that were included, 128 (62%) were labeled low volume, 39 (19%) medium volume, 23 (11%) high volume, and 15 (7%) very high volume. Multivariable analysis showed that very high volume was associated with decreased 30-day PE-related readmission (OR 0.64; 95% CI, 0.55 to 0.73), decreased 30-day all-cause readmission (OR 0.84; 95% CI, 0.79 to 0.89), decreased 1-year mortality (OR 0.85; 95% CI, 0.80 to 0.91), decreased total charges (OR 0.96; 95% CI, 0.94 to 0.98), and decreased length of stay (OR 0.94; 95% CI, 0.92 to 0.96). In summary, facilities with higher volumes of acute PE were found to have less 30-day PE-related readmissions, less all-cause readmissions, shorter length of stay, decreased 1-year mortality, and decreased total charges.